The Competition On The International Wheat Market - Ludmila MOGILDEA; Constanta Laura ZUGRAVU; Ciprian GRIGORESCU; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2022)
The international trade represents a benefit of economic globalization transposed through opportunity, so that the varied supply of goods and services develops and encourages a fair competitive market and sets a fair price relative to quality. International trade in wheat is greater than all other crops combined, despite the fact that it ranks second only to corn in terms of cultivated areas. The international wheat market depends not only on the agricultural productions obtained, but also on the consumption of wheat at the global level.
Keywords: International Trade; Wheat